COVID-19 and emerging markets: The case of Turkey - Cem Çakmaklı; Selva Demiralp; Sebnem Kalemli-Ozcan; Sevcan Yeşiltaş; Muhammed Ali Yıldırım (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
The COVID-19 crisis can turn into the biggest emerging market (EM) crisis ever. EMs observed the financial shock first, with the tightening global financial conditions. They will soon experience the full wrath of the perfect storm with possibly much larger spill-back effects for the global economy. This paper focuses on a large representative EM, Turkey, with low foreign currency reserves, high foreign currency debt and a questionable record on policy credibility. The pandemic has already led to a substantial decline in economic activity and Turkey's policy options are more limited given its low fiscal space and its reliance on capital flows. We estimate the costs and benefits of a full lockdown and offer policy recommendations that will help to avoid an economic meltdown. In order to prevent a 2001 style crisis, the best option is to consider an immediate lockdown and subsidize the economy. The external funding that is necessary for the economic relief package should be secured through international financial institutions rather than imposing capital controls. Domestic funding should be provided with a well targeted and transparent asset purchase program by the central bank.
Keywords: E61; F00; C51; 330; COVID-19; Financial Crisis; SIR; Input-Output Tables; Emerging Markets